The Effect of Balanced Scorecard Implementation on Financial and Non-Financial Performance - Sariani Sariani (Dhana, 2025)
This study examines the effect of Balanced Scorecard (BSC) implementation on corporate financial and non-financial performance within an integrated strategic management framework. Increasing business complexity and market volatility have rendered traditional financial-based performance measurement systems insufficient for ensuring sustainable competitiveness, thereby necessitating a more comprehensive approach to performance management. This research employs a quantitative explanatory design using a cross-sectional survey of medium and large enterprises in the manufacturing and service sectors that have implemented the BSC for a minimum of three years. Data were collected from senior managers and performance management officers through structured questionnaires and supplemented with secondary financial reports. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that BSC implementation has a significant positive effect on financial performance, including profitability, revenue growth, and cost efficiency, and an even stronger positive effect on non-financial performance dimensions such as innovation capability, customer satisfaction, internal process effectiveness, and employee development. Furthermore, non-financial performance partially mediates the relationship between BSC implementation and financial outcomes, confirming the strategic role of non-financial capabilities as drivers of long-term financial success. These findings reinforce the position of the Balanced Scorecard as a comprehensive strategic management system that aligns organizational activities with sustainable performance objectives.